DAMPAK DAN KENDALA WISATA WADUK SERMO DARI ASPEK LINGKUNGAN HIDUP DAN RISIKO BENCANA - Sudarmadji dan M. Widyastuti (Universitas Gadjah Mada, 2014)
Sermo Reservoir is a multipurpose reservoir. Due to its natural beauty and being the only reservoir in Yogyakarta Special Region, it is visited by many tourists. Tourism activities in the reservoir may cause environmental impacts and disaster risks for the tourists. This study aims to determine the potential of Sermo Reservoir as a natural tourism object and, in general, analyze the environmental impacts and disaster risks caused by tourism activities. The study was conducted by field surveys, observations and interviews with the local community. Reservoir water samples were collected for physical and chemical parameter analysis and were evaluated against the standard requirements of water for tourism activities. Data analysis was performed using descriptive qualitative and quantitative methods, using tables and diagrams of the processed data. In general it was found that the Sermo Reservoir has high potential for tourism. However, due to the lack of supporting facilities, the number of tourist coming to the Sermo Reservoir is still not yet optimal. The environmental impacts caused by tourism activities have occurred. The positive impacts that arise are the emerging business opportunities and the increased revenue of the local people, while the negative impacts are the pollution caused by solid waste and the water quality degradation. The risk of disaster may come from accidents when conducting activities in the reservoir, and it should be considered in the development of Sermo Reservoir for tourism.